Investigation of the adsorption behavior of BSA with tethered lipid layer-modified solid-state nanopores in a wide pH range. Issue 27 (17th May 2019) - Tian, Haibing; Xie, Wanyi; He, Shixuan; Zhou, Daming; Fang, Shaoxi; Liang, Liyuan; Wang, Deqiang
Abstract : Nanopore technology was introduced for the study of the interaction between bovine serum albumin (BSA) and 1, 2-dioleoyl- sn -glycero-3-phosphoethanolamine (DOPE) phospholipids. Abstract : Nanopore technology was introduced for the study of the dynamic interactions between bovine serum albumin (BSA) and 1, 2-dioleoyl- sn -glycero-3-phosphoethanolamine (DOPE) phospholipids based on a modified nanopore. The results reveal that the interaction mechanism between DOPE and BSA is affected by the pH of the subphase. Far above the BSA isoelectric point (pH > 7), a weaker hydrophobic interaction and stronger electrostatic repulsion exist between the DOPE and BSA molecules. At pH = 7, the BSA structure nearly does not change, and the interaction is weak. At pH 5 and pH 6, BSA is marginally affected by the adsorption interaction, and below pH 5, the DOPE film becomes disordered, so there is a strong repulsive force interaction between the BSA and DOPE.